Peranan Kepala Desa dalam Pelaksanaan Pembangunan di Desa Ombarade, Kecamatan Wewewa Tengah, Kabupaten Sumba Barat Daya - Agustinus Bali Mema; I Nyoman Putu Budiartha; I Nyoman Sutama (Jurnal Preferensi Hukum, 2021)
The Village Head is responsible for carrying out development in his area and meeting all the needs of its citizens, one of which is the provision of public facilities through infrastructure development. The people of Ombarade Village, Southwest Sumba Regency really need facilities and infrastructure to make it easier for their people to carry out their activities. This study aims to reveal the role of the village head in the implementation of development, as well as to examine the obstacles of the village head in the implementation of development. This study was designed with empirical research using an approach to see and examine facts in the field using interview data collection techniques. The data used are primary data and secondary data. Furthermore, the data were analyzed descriptively qualitatively. The results showed that the authority of the Ombarade Village Head, Wewewa Tengah District, Southwest Sumba Regency regarding the implementation of development based on Law Number 6 of 2014, Regulation of the Minister of Home Affairs Number 114 of 2014. On the other hand, one of the inhibiting factors for village development lies in the lack of facilities. and infrastructure and supporting facilities. In addition, the lack of socialization regarding work programs or the like related to the village development process also affects the smooth implementation of village development.